Boundary layer approach to heat and mass transfer in porous bodies of cylindrical geometry - Rai K.N.; Pandey R.N. (My University, 2025)
Integral balance method is applied to determine the transfer potentials of heat and mass in porous bodies of simple geometry. The solutions thus obtained are compared with the exact solutions of the linear problems. Further, the method is utilized in developing solutions for a non-linear problem also. Criterial influence over the transfer potentials is shown graphically. The advantage of the present method is to provide quick approximate results to non-linear problems involving temperature and moisture dependent physical properties of the medium. © 1976.